Estrategias metodológicas y su impacto en el proceso de aprendizaje en el área de matemática de los estudiantes del 3ro. EGB. de la EEB. Otto Arosemena Gómez- Quevedo - Orbe Quinto, Angela Elena (2023)
The development of this research is framed in the use of a strategy for learning mathematics for 3rd grade students. EGB. of BSE. Otto Arosemena Gómez - Quevedo, in order to endure a teaching-learning process. The process of learning and teaching mathematics has become in recent years a widely complex and tedious task. The methodological strategy helps to improve the learning of mathematics where students develop their critical reflective and reasoning abilities, avoiding with This is mechanical-repetitive learning. The problem arises from the author's experiences in educational centers and especially from the concern about the academic performance of seventh-year students in the area of mathematics, which is why the need to carry out a methodological strategy based on pedagogical currents was seen. contemporary technologies that contribute to improving learning in this area. This strategy is organized as follows: problem: statement of the problem, background, importance and scope, delimitation and explanation of the problem. Objectives: general and specific. Theoretical foundation where he talks about contemporary pedagogical currents, constructivism, importance of education, conception of learning. Strategies: definition, characteristics and types of learning strategies. Methodology: type of proposal, parts of the proposal, recipient and methodology. Finally, five activities are developed as examples to practice in the classroom with mathematics exercises for 3rd grade students. EGB. of BSE. Otto Arosemena Gómez, with the application of a methodological strategy to strengthen mathematics.